Clinical implications and histological correlation of atypical glandular cells found in cervicovaginal smears - Beliza Loos; Karina Munhoz de Paula Alves Coelho; Paulo Henrique Condeixa de França; Giuliano Stefanello Bublitz; Hercílio Fronza Júnior (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Atypical glandular cells (AGC) are carriers of insufficient nuclear abnormalities for the diagnosis of adenocarcinoma, but exceed the criteria for classification as reactive glandular cells. This is an uncommon diagnosis, which may be associated with neoplastic lesions. Objective: To evaluate the clinical significance of primary cytological diagnosis of AGC through correlation with results of subsequent cyto-histologic examination. Materials and methods: 10 years retrospective study based on cervical cytologic results indicating AGC, classified as "possibly non-neoplastic" or "cannot exclude high-grade intraepithelial lesion". It was performed cyto-histopathological correlation in cases that were submitted to subsequent histopathological examination up to two years after cervical cytology analysis. Results: AGC were reported in 380 (0.06%) exams, providing 160 cases with subsequent biopsy. 85 (53.1%) of these, presented benign changes and 75 (46.9%) neoplastic lesions. From 114 "possibly non-neoplastic" cytological results, 71 (62.3%) had benign histological changes, and 43 (37.7%) neoplastic lesions, corresponding to a negative predictive value (NPV) of 62.3%. In contrast, among the 46 AGC "cannot exclude high-grade intraepithelial lesion" results, 14 (30.4%) presented benign changes and 32 (69.6%) neoplastic lesions (positive predictive value [PPV] = 69.6%). Discussion: The high rate of cancer associated with the diagnosis of AGC reassures the importance of recognizing these atypical cells in pap smears. The classification of "possibly non-neoplastic" and "cannot exclude high-grade intraepithelial lesion" may suggest the origin of cytological changes. Conclusion: Our results reinforce the importance of adequate follow-up of patients with AGC diagnosis on cervical cytology.